# Please answerrrrr Thank you!!!!!!!!!!!!

## Answers

The correct answers are: _________________ " (x − 13) ° = 53 ° " ; _________________ " x = 66 " ; _________________ " m∠2 = 55° " ; _________________ " m∠1 = 55° " .__________________Step-by-step explanation:Note: The following "given values/answers" within the attached image: Specifically: (x − 13)° = 72° ; and; x = 85° ; _________________ are: "incorrect"—and are "arbitrarily assigned values"_________________The values and expressions given in the attached image, however, are correct/do make sense; and we can use such data to solve the problem._________________Let's start by finding the measure of ∠2 ; that is: " m∠2 " :To find m∠2: _________________Note that: both: "∠2 " ; and the angle that measures "175" with the attached image: → both form a straight line—that is; → they are "supplementary angles" ; → which means they add up to "180° " ; _________________So: To solve for: "m∠2" : _________________ → m∠2 = 180 − (125) = 55° ,_________________Now; to solve for: " m∠1 " : _________________Note that ∠1 and ∠2 are vertical angles: which means that they have equal measurements; {since: vertical angles are congruent; which means that vertical angles are equal.} ; _________________→ As such, m∠1 = m∠2 = 55 °._________________Now, take either ∠1 or ∠2 ; (each has the same "measurement"—"55° " ; And combine with angle with the given measurement of 72° ; And combine with the angle with the "given measurement of [the expression: ["x − 13"]° ; _________________All three of these angles form a straight line—that is; → they are "supplementary angles" ; → which means they add up to "180° " ; So, 55° + 72° + (x − 13)° = 180° ; Let us solve for "x" ; and for "(x − 13)" ; _________________55 + 72 = 127 ; → 127 + (x − 13) = 180 ; Now, subtract "127" from each side of the equation:_________________ → 127 + (x − 13) − 127 = 180 − 127 ; to get: " (x − 13) = 53 " ; → which is one of our answers; Now, to solve for "x" ; we add "13" to Each Side of the equation; to isolate "x" on one side of the equation; & to solve for "x" : _________________ x − 13 + 13 = 53 + 13 ; to get: _________________ x = 66 ; _________________So: The correct answers are: _________________ " (x − 13) ° = 53 ° " ; → Double check by substituting our value of "66" for "x" : " (66 − 13) =? 53 ? Yes! ; _________________ " x = 66 " ; _________________ " m∠2 = 55° " ; _________________ " m∠1 = 55° " . _________________Hope these answers—and explanations—are helpful! Best wishes!_________________